Erythrokeratodermia variabilis: Two case reports - Ayse Serap Karadag; Serap Gunes Bilgili; Omer Calka; Irfan Bayram (Wolters Kluwer Medknow Publications, 2013)
Erythrokeratodermia variabilis (EKV) is a rare heterogeneous skin disorder. The classical EKV first described by Mendes da Costa is characterized by two types of skin lesions: (1) figurate hyperkeratotic plaques, and (2) transient erythematous areas. Herein, we report two patients presenting with erythematous and hyperkeratotic lesions that were histopathologically diagnosed with EKV.